Metáfora, oxímoro e argumentatividade (Metaphor, Oxymoron and Argumentativity) - Guimarães, Eduardo (2015)
ABSTRACTWe intend, in this paper, to produce a study about the metaphor from a specific theoretical place, which is the Semantics of the Events. To do that we are going to analyze the enunciative processes involved in enunciative events that build the meaning of some expressions, such as “he destroys the saxophone, the presentation is/was thrilling!”. This allows us to understand better the way that metaphors work as language events.KEYWORDS: Metaphor. Enunciation. Semantics of the Events.